BURNOUT IN MEDICAL STUDENTS AND ITS ASSOCIATION WITH MENTAL HEALTH: A DOCUMENTARY ANALYSIS - do Nascimento, Tainah Martins; Lima Brandão Simões, Angélica (CIPEEX, 2025)
Burnout syndrome, characterized by emotional exhaustion, depersonalization, and low academic efficacy, has become a growing concern among medical students due to high academic demands, intense emotional exposure, and limited institutional support. This study aims to analyze the impact of burnout on medical students and its implications for mental health, focusing on psychological distress and suicidal ideation. This is a descriptive and documentary qualitative study conducted through a literature review. The databases LILACS, PubMed, and SciELO were consulted in Portuguese and English, using controlled descriptors “Burnout”, “Medical Students”, “Mental Health”, and “Suicidal Ideation” combined with the boolean operators AND and OR. The temporal scope included articles published between 2018 and 2024. The selected studies investigated the prevalence of burnout, its associated factors, and its impact on the mental health of medical students. The reviewed literature included a multicenter study with 511 Brazilian medical students, showing a burnout prevalence ranging from 30% to 50%. The most used instrument was the Maslach Burnout Inventory – Student Survey (MBI-SS), which evaluates emotional exhaustion, cynicism, and academic efficacy. Students with burnout showed lower scores in the psychological and physical domains of quality of life. A strong association was found between burnout and symptoms of anxiety, depression, and suicidal ideation, underscoring its relevance in preventive strategies such as the "Yellow September" campaign. The data also pointed to greater vulnerability among female students and those in the intermediate stages of the course. Recognizing and addressing burnout in medical education is essential for protecting students' mental health and for shaping emotionally resilient future physicians. The findings reinforce the need for institutional policies focused on psychological support, early detection of emotional distress, and the development of socio-emotional skills, contributing to a healthier academic environment.